THE DEEP STRUCTURES OF THE SELECTED NEWSPAPER HEADLINES: A TGG ANALYSIS - Moh. Arif Mahbub (FKIP Universitas Islam Jember, 2016)
This study is aimed at (1) generating the all possible deep structure and (2) describing what type of transformation applied to the selected newspaper headlines. This is a qualitative research since it involves analyzing and interpreting the selected newspaper headlines. The analysis in this study is thus interpretive rather than statistical. Purposive sampling is used in this study since the selected newspaper headlines published by ‘The Jakarta Post’ in the period of May 4 – July 1, 2013 are suited to the intent of the study. The findings show deletion transformation is frequently applied to them. Every single headline contains of words deletion making them ungrammatical. The headline writer applies this type of transformational process in order to attract the readers’ attention so that they are curious to know the contents of the whole story. To conclude, applying TGG analysis can provide an adequate explanation about how the deep structures of the selected newspaper headlines are generated into their surface structure. Keywords: TGG, Newspaper Headlines